(3eQGLYI GdMSGHGJ hGdJObjb (B/s - (3ShGO, RGgQg YGWas ((3YeGf(B: s (3OGQ GdQGjI ddfTQ(B, s, 2009)
(3eGgjI GdeQGLYI GdMSGHjI,GdeQGLYI GdMSGHjI GdTGedI,CgOGa hCSGdjH YedjGJ GdeQGLYI,GdeQGLYI GdOGNdjI,JbQjQ GdeQGLY,eObb GdMSGHGJ,eSDhdjI GdeQGLY hCOdI GdEKHGJ GdbGfhfjI aj GdeQGLYI,CfhGY GdJObjb aj GdMSGHGJ,GdeMGSHI hGdQbGHI Ydi YfUQ JcdaI GdYed hGdeSJdReGJ GdSdYjIs
(3HHdjhZQGajG(B:(3U U(B.245-246s
Keywords: (3eQGLYI GdMSGHGJs